2009
DOI: 10.3109/08982100903244500
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of medium-chain fatty acid liposomes by lyophilization

Abstract: In this study, medium-chain fatty acid (MCFA) liposomes were prepared by the film ultrasonic dispersion, modified ethanol injection, and reverse-phase evaporate methods. The results indicated that the liposomes prepared by the thin-film ultrasonic dispersion method had a high entrapment efficiency of 82.7% and a good distribution in size diameters. The MCFA liposomes were freeze-dried and the optimal preparation conditions of freeze-drying were as follows: The cryoprotectants were mannitol and sucrose (1:1 w/w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…The freeze-dried complex nanoliposomes without any cryoprotectant (the control group) exhibited a larger mean particle diameter of (151.4 ± 10.76) nm, and drugs entrapment efficiencies could not be detected because of the damages caused by lyophilization. Similar results were found in our previous report [31], which indicated that the freezing-drying process has a small effect on the liposome size, resulting in a slight increase in average diameter from 250.1 to 263.3 nm. On the other hand, formulations prepared without saccharose as cryoprotectant presented an increase in vesicle size after lyophilization.…”
Section: Resultssupporting
confidence: 92%
“…The freeze-dried complex nanoliposomes without any cryoprotectant (the control group) exhibited a larger mean particle diameter of (151.4 ± 10.76) nm, and drugs entrapment efficiencies could not be detected because of the damages caused by lyophilization. Similar results were found in our previous report [31], which indicated that the freezing-drying process has a small effect on the liposome size, resulting in a slight increase in average diameter from 250.1 to 263.3 nm. On the other hand, formulations prepared without saccharose as cryoprotectant presented an increase in vesicle size after lyophilization.…”
Section: Resultssupporting
confidence: 92%
“…There have been limited studies on the large-scale preparation of NL from edible lipids by using DHPM from the viewpoint of developing the formulations into an efficient carrier of nutritional materials. In our previous research ( 16 ) , thin-layer dispersion, ethanol injection and reverse-phase evaporation were used to prepare MCFA liposomes, and a new method of thin-layer dispersion combined with DHPM was developed to efficiently prepare MCFA NL with easy-energy-supply property to mice ( 17 ) .…”
mentioning
confidence: 99%
“…These properties have been used advantageously in clinics for more than 50 years for treating lipid absorption disorders, undernourished patients, and more recently, subjects with long-chain fatty acid oxidation defects. [15][16][17] For pharmaceutical development and clinical use, several criteria must be fulfilled in terms of size as well as chemical and physical stability. Small-sized liposomes have several advantages as drug delivery systems.…”
Section: Introductionmentioning
confidence: 99%